Thioester-containing proteins of the tick Ixodes ricinus: gene expression, response to microbial challenge and their role in phagocytosis of the yeast Candida albicans - Urbanová, Veronika; Šíma, Radek; Šauman, Ivo; Hajdušek, Ondřej; Kopáček, Petr (Developmental and comparative immunology, 2015)
The ability of ticks to act as vectors for a wide range of serious human and animal infectious diseases is apparently linked to the insufficiency of the tick immune system to effectively eliminate pathogens they transmit. At the tick-pathogen interface, an important role is presumably played by components of an ancient complement system that includes a repertoire of thioester-containing proteins (TEPs), which in Ixodes sp. comprises three α2-macroglobulins (A2M), three C3 complement component-related molecules (C3), two macroglobulin complement-related (Mcr) and one insect-type TEPs (Tep). In order to assess the function of TEPs in tick immunity, a quantitative real-time PCR expression analysis of tick TEPs was performed at various developmental stages of Ixodes ricinus, and in tissues dissected from adult females. Expression of TEP genes was mostly tissue specific; IrA2M1, IrC3-1, IrC3-3 were found to be expressed in cells of tick fat body adjacent to the tracheal trunks, IrA2M2 in hemocytes, IrTep in ovaries, IrMcr1 in salivary glands and only IrA2M3, IrC3-2 and IrMcr2 mRNAs were present in multiple organs. Expression of tick TEPs was further examined in response to injection of model microbes representing Gram-negative, Gram-positive bacteria and yeast. The greatest expression induction was observed for IrA2M1 and IrC3-1 after challenge with the yeast Candida albicans. Phagocytosis of the yeast was strongly dependent on an active thioester bond and the subsequent silencing of individual tick TEPs by RNA interference demonstrated the involvement of IrC3-1 and IrMcr2. This result suggests the existence of a distinct complement-like pathway, different from that leading to phagocytosis of Gram-negative bacteria. Understanding of the tick immune response against model microbes should provide new concepts for investigating interactions between ticks and relevant tick-borne pathogens.
Keywords: Phagocytosis; Gram-Negative Bacteria; Ixodes; RNA interference; Complement; Tick Ixodes ricinus; Candida albicans; proteiny členovců; RNA Interference; gramnegativní bakterie; Hemolymph; fagocytóza; hemolymfa; grampozitivní bakterie; ženské pohlaví; zvířata; Arthropod Proteins; Innate immunity; Gram-Positive Bacteria; malá interferující RNA; klíště; Thioester-containing proteins; Female; RNA, Small Interfering; Animals